2006
DOI: 10.1167/iovs.05-1649
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Roles of Human Cathelicidin (LL-37) at the Ocular Surface

Abstract: LL-37 expression is upregulated in regenerating human corneal epithelium, has antibacterial activity against ocular pathogens under physiologically relevant conditions, and stimulates HCEC migration and cytokine production. These findings suggest that LL-37 acts as a multifunctional mediator that helps protect the cornea from infection and modulates wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
110
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 63 publications
5
110
1
Order By: Relevance
“…19 This ATCC strain is known to produce severe ocular infection in experimentally infected animal models of bacterial keratitis. 40,41 PA cultures were suspended in phosphate buffer (PB) to a concentration of 2.0 × 10 8 cfu/mL.…”
Section: Experimental Keratitismentioning
confidence: 99%
See 3 more Smart Citations
“…19 This ATCC strain is known to produce severe ocular infection in experimentally infected animal models of bacterial keratitis. 40,41 PA cultures were suspended in phosphate buffer (PB) to a concentration of 2.0 × 10 8 cfu/mL.…”
Section: Experimental Keratitismentioning
confidence: 99%
“…Further, the vessel growth observed in the KO mice could have been initiated by the higher number of infiltrating neutrophils and possibly macrophages, as these cells contain significant amounts of angiogenic mediators that can be released in response to cellular activation. [65][66][67] Notably, the ability of cytokines to induce other cytokines and pro-and/or antiangiogenic factors secondarily and function as chemotactic factors for inflammatory cells makes it difficult to sort out the final and critical mediators of angiogenesis, infiltration, and inflammation conclusively in vivo.In the cornea, epithelial cells are a source of various antimicrobial peptides (including CRAMP, data not shown), particularly after injury or in response to inflammatory 19,[68][69][70] Furthermore, infiltrating neutrophils and macrophages present in the cornea as a result of microbial challenge also play an important role in limiting bacterial invasion by the production of certain peptides including the cathelicidins. Findings from the present study showed that functional activities of cathelicidin are necessary for bacterial clearance and innate corneal immunity at the ocular surface.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…16 Briefly, HUVEC were grown in a 25 cm 2 tissue culture flask (Asahi Technoglass) until they were approximately 80% confluent. The cells were then trypsinized, washed, counted, and resuspended in serum-free and growth factorfree EBM-2 basal medium.…”
Section: Endothelial Cell Proliferation Assaymentioning
confidence: 99%